pH and temperature dependence of the rate of dissolution of AgIO3 - Uyanık, Ömer Lütfi. (Thesis (Ph.D.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 1984., 1984)
In this thesis a theory based ona dissolution model was checked experimentally. The theory which is developed by B.V. Enüstün expresses the initial rate of dissolution for a 1:1 type ionic solid in terms of the model parameters by considering the electrochemical properties of the crystal/ solution interfate. The theory has been verified previously on the basis of some experimental work by observing the . dependence of the initial dissolution rate of AgI03 on ionic strength in various media at 25 °C. In this work, the dissolution kinetics of AgI03 was investigated as a function of pH at 25 °C, and temperature using a concentration cell with silver electrodes. It was observed that in acidic media, initial dissplution rate of AgI03 drops to an asymptotic value at high and medium pH's showing a Gouy type electrical double layer behavior due to the proton nature of H+ ions. The temperature dependence of the initial dissolution rate of AgI03 in distilled water follows an Arrhenius type relation with a reasonable value of activation enthalpy for dissolution. The dependence of initial dissolution rate of AgI03 on ionic strength in various media at 25 °C was also followed and the results previously obtained hav.e been reproduced. Two important conclusions reached at the end of the work-were that in the presence of small hydrated cations in the dissolution medium the electrical double layer behaves as a Gouy layer and in the presence of large hydrated cations it behaves as a Stern layer.
Keywords: Dissociation.; Metals -- Dissolution.